â€œKajian Erosi Di Daerah Aliran Sungai Sario Sulawesi Utaraâ€ â€œStudy of Erosion in Sario Watershed North Sulawesiâ€ - Patriot Yusuf Carol Turangan; Dr. Ir. Jody M. Mawara; Ir. Yani E.B. Kamagi (COCOS, 2018)
ABSTRACT Â Watersheds are very important for human life. Land erosion is one of watershed damage conditions which causes a lot of grief to the community. To determine the extent of erosion and the level of erosion hazard in Sario watershed is the goal of this study. A survey method was carried out with a land unit approach. Erosion was calculated using the USLE. The amount of erosion was 1077,76 tons/hectare/year with an average erosion of 53,89 tons/hectare/year. The level of erosion hazard in Sario watershed consist of : an area of 857,71 ha (41%) of very low erosion hazard, an area of 549,12 ha (26,83%) of low erosion hazard, an area of 200,63 ha (9,80%) of moderate erosion hazard and an area of 439,57 ha (21,47%) of severe erosion hazard. Â Keywords : Watersheds, Erosion, Erosion Hazard